Runes, ogham and Latin scripts: transition between orality and literacy in post-Roman Britain - Mianowski, Jacek (Scripta Neophilologica Posnaniensia, 2020)
Runic and ogham scrips are an important part of the heritage of the British Isles. While it is difficult to determine exactly where and when they were invented, and the contemporary consensus on this issue leaves many questions open, the importance of these writing systems in the oral-literate transition cannot be called into question. For these reasons, the following study has two aims. Firstly, it attempts to familiarise the reader with the historical background to the process of transition from orality to literacy. Secondly, it tries to allocate runes, ogham and Latin scripts within an anthropological perspective.